A aprendizagem da escrita por crianças com suportes digitais - Köhle, Érika Christina (Editora Oficina Universitária, 2022)
This book defends the idea that "the teaching of language requires accepting that subjects are in continuous constitution as they interact with others, in a continuous process of completing themselves through the other and completing the other, because the concepts that are internalized by both they are ways of understanding the world." It reveals to us that "the teaching of writing acts through the development of creations that had the computer and the smartphone as supports had a special meaning for the children in the research carried out, because in addition to learning to elaborate writing acts inserted in the current enunciation it was possible to provide them with a new learning environment - the digital environment". It also shows that "bringing to school varieties of both supports and genres that circulate socially always causes beneficial effects, not only for learning formal language knowledge but also for experiencing its socio-enuciative practices".